Conversor CA-CC PWM-ZVS duplo push-pull alimentado em corrente com alto fator de potência - Delgado, Arlindo Hernany Ramos (2024)
This work presents the study of a quasi-single stage AC-DC converter with characteristics of high frequency isolation, high power factor, switches soft switching, output voltage regulation and operation with bivolt input voltage (110 Vac/220 Vac). The proposed structure is based on two current-fed Push-Pull ZVS DC-DC converters, which were magnetically interconnected using an inductor and a high-frequency transformer. For bivolt operation a voltage selector is used, thus, for the input voltage of 110 Vac the inputs of the DC-DC converters are connected in parallel, and for the input voltage of 220 Vac the inputs are associated in series. In this way, many components on the primary side of the transformer are subjected to the same current and voltage stresses, resulting in almost similar yields for both input voltage values indicated above. For the converter under study, qualitative and quantitative analyzes are presented, as well as a project example made to specifications of alternating input voltage Vi = 110 Vac/220 Vac, output voltage Vo = 400 V, output power Po = 2 kW and switching frequency fs = 25 kHz. After obtaining the quantities, the proposed converter was subjected to simulation and the results are presented for operation in steady state and in transient regime.